Dampak Promosi Dan Harga Pada Loyalitas Pelanggan Melalui Kepuasan Pelanggan Pada Exo Dimsum Bangkalan - Dwi Ambarwati; Suyono Suyono (Management Department of Economics and Business Of Trunojoyo Madura University, 2026)
This study aims to determine the effect of promotion and price on customer loyalty with customer satisfaction as a mediating variable. The methodology used is quantitative with empirical methods and statements. Data in this study were collected from November to December through questionnaires filled out by Exo Dimsum Bangkalan customers, with a population of unknown size. This study uses a non-probability sampling approach with a Purposive Sampling approach determined by the Lemeshow formula, so that the minimum requirement of 96 respondents is obtained. To increase accuracy and anticipate invalid data, the number of samples used is 100 respondents. Data analysis used Partial Least Squares (PLS) processed with SmartPLS 4.1. The results of the study indicate that promotion has a significant effect on customer loyalty and satisfaction, while price is proven to have no direct effect on loyalty, but has a significant effect on customer satisfaction. Furthermore, customer satisfaction has a strong influence on loyalty. The results of the mediation analysis indicate that customer satisfaction does not mediate the relationship between promotion and loyalty, but mediates the relationship between price and customer loyalty. Exo Dimsum is advised to increase promotional effectiveness, optimize competitive pricing strategies, and strengthen service quality to enhance customer satisfaction and loyalty. Continuous efforts to improve the overall customer experience are also necessary to maintain long-term loyalty.